2021
DOI: 10.1111/trf.16495
|View full text |Cite
|
Sign up to set email alerts
|

Rate of RhD‐alloimmunization after the transfusion of multiple RhD‐positive primary red blood cell‐containing products

Abstract: Introduction Early transfusion reduces mortality in bleeding patients. In this setting, RhD‐positive blood products might be transfused. This study determined the association between the RhD‐alloimmunization rate and the number of RhD‐positive products transfused. Methods RhD‐negative patients between 13 and 50 years who were transfused with ≥1 RhD‐positive red blood cell (RBC) or whole blood units between January 1, 2000 and December 31, 2019 in a healthcare network were identified. Study patients had to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…In our model, mismatches are presumed to be binary events: a patient is either exposed to a foreign antigen within a transfusion episode or not, and the probability of antibody development is not dependent on the number of mismatched transfusions given during one transfusion episode. This assumption is in line with the recent publication of Yazer et al who found no significant dosage effect in RhD-alloimmunization rates among exposed transfusion recipients [18]. By ignoring the level of exposure, we maximize the proportion of patients for which exposure is prevented.…”
Section: Methodssupporting
confidence: 65%
“…In our model, mismatches are presumed to be binary events: a patient is either exposed to a foreign antigen within a transfusion episode or not, and the probability of antibody development is not dependent on the number of mismatched transfusions given during one transfusion episode. This assumption is in line with the recent publication of Yazer et al who found no significant dosage effect in RhD-alloimmunization rates among exposed transfusion recipients [18]. By ignoring the level of exposure, we maximize the proportion of patients for which exposure is prevented.…”
Section: Methodssupporting
confidence: 65%
“…In addition, we saw an inverse correlation between anti‐D formation and the number of units of RBCs, and no increase in anti‐D rate after re‐exposure to D‐positive RBCs [16, 18]. Furthermore, in the study of Yazer et al [27], although there was no significant dosage effect in the alloimmunization rates with exposure to D‐positive units, the immunization rate was 30.6% in the 1‐unit group, 43.6% in 3–5 units group, and lowest rate of 18.4% in 11–20 units group [27]. It is consistent with the study of Gonzalez‐Porras et al [17], in which most patients who developed anti‐D did so within the first two or four RBCs transfused (64% after the first two RBCs transfused and 88% after the first four).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, some patients received several sessions of D-positive RBC transfusion and also received D-negative RBCs when the D-negative blood type was confirmed or the supply of D-negative blood was replenished. In the study of Yazer et al [27] with mixed disease patients, 80.9% patients (277/335) received a total of 2727 units of D-negative RBC-containing components in the period after the index D-positive product to "wash out" the transfused D-positive RBCs, but there were still 34.9% patients (117/ 335) who became immunized. A similar situation occurred among trauma patients in the study of Tchakarov et al [32].…”
Section: D-positive Rbc Transfusion In D-negative Patients With Mixed...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, resuscitation with whole blood may be a better option for exsanguinating hemorrhage in certain parts of the world where there is a lack of well-equipped blood banks and insufficient availability of blood products [ 123 ]. However, the percentage of all donors who are eligible to donate RhD-negative LTOWB (male, group O, RhD-negative, and have low titer anti-A and -B) is only 3% RhD-alloimmunization rate is approximately 21% [ 124 ].…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 99%